INFORMATIONAL TECHNOLOGIES IN THE PROCESS OF TEACHING ANDSTUDYING SAFETY OF VITAL ACTIVITIES AT HIGHER SCHOOL - Опара, Н. М. (Scientific Progress & Innovations, 2014)
Informational technologies in the process of teaching the course Safety of vital activities at higher educational establishments are considered in the article. Detailed attention has been paid to using general approaches, suggested by a group of authors, the leading components of conceptual apparatus, on the basis of which it is possible to improve the contents, forms and methods of study process shave been discussed. In the process of.quickly increasing informational loading the quality of study process greatly depends on its intensification and optimization on the basis of effective using classical and also active introducing new methods which are based on the broadest using of computers of various modifications.